Simulation of quantum field theory and gravity in superfluid ³He - Volovik, G.E. (Физика низких температур, 1998)
Superfluid phases of ³He are quantum liquids with the interacting fermionic and bosonic fields. In many respects they can simulate the interacting quantum fields in the physical vacuum. One can observe analogs of such phenomena as axial anomaly, vacuum polarization, zero-charge effect, termionic charge of the vacuum, baryogenesis, ergoregion, vacuum instability, etc. We discuss some topics using as an example several linear defects in ³He-A: (1) disgyration, which simulates the extremely massive cosmic string, (2) singular vortex, which is analogous to the spinning cosmic string, and (3) continuous vortex, whose motion causes the «momentogenesis» which is the analog of baryogenesis in early Universe. The production of the fermionic momentum by the vortex motion (the counterpart of the electroweak baryogenesis) has been recently measured in Manchester experiments on rotating superfluid ³He-A and ³He-B. To simulate the other phenomena, one needs a rather low temperature and high homogeneity, which probably can be attained under microgravity conditions.